ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Muhamad Alam Subayin; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the factors that affect earnings management in food and beverage sub-sector companies listed on the IDX 2016-2020. The variables used are earnings management as the dependent variable. And five of other variables such as leverage, company size, KAP size, institutional ownership and managerial ownership as independent variables. The population used in this study were 30 food and beverage sub-sector companies listed on the IDX 2016-2020. While the sample used is 14 companies that have been selected using a purposive sampling method with certain criteria. This study uses multiple linear regression analysis with the SPSS software. The results obtained from hypothesis testing are leverage, company size, KAP size, institutional ownership and managerial ownership simultaneously have a effect on earnings management. While partially, leverage and firm size have a significant negative effect on earning management, managerial ownership has a positive effect on earnings management. KAP size and institutional ownership have no effect on earnings management in food and beverage sub-sector companies listed on the IDX 2016-2020.Keywords: Earnings management, leverage, company size, KAP size, institutional ownership and managerial ownership.